Assessment of pre-service physics teachers’ conceptual understanding in electricity and magnetism - Mihret, Zemenu; Alemu, Mekbib; Assefa, Shimeles (Universitas PGRI Kanjuruhan Malang, 2023)
This study focused on an assessment of pre-service physics teachers’ conceptual understanding of physics in the domain of electricity and magnetism concepts. The study employed a descriptive survey method of research. The study sample consisted of 100 pre-service physics teachers from five teacher education colleges during the academic year 2021/21. The study used preliminary data from a PhD dissertation that was gathered by administering a conceptual understanding test on electricity and magnetism, which contained 32 items adapted from standardized tests. The data were analyzed using descriptive statistics, one sample t-tests, independent samples t-tests, and one-way ANOVA. The results of the one sample t-test showed that the conceptual understanding test scores for electricity and magnetism were considerably below 50 and 70 which are the national standard pass mark points and the baseline for certification of competency to the teaching profession, respectively. ANOVA analysis revealed that there was a statistically significant mean difference among the pre-service physics teachers in the colleges. The post hoc test analysis showed that there was a statistically significant mean difference between pre-service teachers from two colleges. The independent samples t-test revealed that there was statistically significant mean difference between test scores of males and females in favor of male pre-service physics teachers. In addition, the participation of female candidates was too low compared to their male counterparts. In conclusion, the achievement of pre-service physics teachers was below the expected values; differences among colleges were detected; and there was an achievement and participation imbalance in relation to gender, though consecutive measures were taken. Based on the conclusions, recommendations are given that could be applicable.